Recognition of Customary Law in the National Criminal System: a Holistic Approach - Abdullah, Rahmat Hi; Mutalib, Abdul; Sutrisno, Andri (Jurnal Cakrawala Hukum, 2024)
This paper is prepared to focus on the problem of an integral approach to the recognition of customary law in the national punishment system. The analysis results in a policy approach that states that the purpose of punishment is no longer retaliation against the perpetrator but is more oriented towards the goal of preventing people from committing crimes again. In addition, it is also seen that punishment is carried out with the aim of resolving conflicts that arise, restoring social balance, and creating a sense of peace. This conscious and deliberate policy is based on the basic idea of balance, including a mono-dualistic balance between the interests of society and the interests of individuals. The formulated idea of balance is a form of recognition of customary law. The value approach is carried out by formulating the objectives of customary law punishment crystallized in Pancasila, including restoring balance in society, both spiritual balance and balance of social relations. This is very relevant to the balance between religious values, human values, and societal values in the five precepts of Pancasila.